Mekanisme Pencalonan Presiden dalam Sistem Presidensial: Diferensiasi Antara Indonesia Dan Filipina - Mutiah Fathihatus Syifa Paci; Rahmawati Rahmawati; Indah Fitriani Sukri; Badruzzaman Badruzzaman (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study examines the comparative presidential nomination mechanisms in the presidential systems of Indonesia and the Philippines, highlighting the differences in procedures and their impact on political developments in both countries. This study uses a literature review method with a comparative approach, focusing on the analysis of legal documents, academic literature, and election regulations in both countries. The results show that although Indonesia and the Philippines both adopt presidential systems, differences in election mechanisms, the role of political parties, and term-setting regulations create dissimilar political dynamics. In the Philippines, the dominance of candidate figures is more pronounced, while in Indonesia, the nomination process is largely determined by political parties. The Philippines' presidential term limit, which allows for only one six-year term without re-nomination, also distinguishes the two countries. This study provides insights into differences in presidential systems that could contribute to electoral reform and presidential nominations in countries with similar systems.